How to draw cartoons - Antram, David , 1958- (Brighton, East Sussex UK : Book House, 2008)
Helps you learn how to draw a variety of amusing characters and animals, and combine them to make dramatic scenes. This book includes focus on specialist areas such as faces and hands. It covers a comprehensive range of popular subjects, with sections on materials, composition, perspective and technique.
1. Making a start -- 2. Perspective -- 3. Drawing tools -- 4. Materials -- 5. Drawing a figure -- 6. Heads -- 7. Expressions -- 8. Characters -- 9. Figure work -- 10. Figure in costume -- 11. Monster -- 12. Rats -- 13. Bulldog -- 14. Man on a donkey -- 15. Glossary and index
Includes index
Keywords: Cartooning -- Juvenile literature; Cartooning -- Technique -- Juvenile literature; Comic books, strips, etc. -- Technique -- Juvenile literature